13C NMR spectroscopy of copoly(arylenephthalide) derivatives with diphenyloxide and terphenyl fragments in the main chain. (7th August 2013) - Kraikin, Vladimir A.; Fatykhov, Akhnef A.; Sakhipova, Il'nara I.; Sedova, Elvira A.; Egorov, Aleksandr E.; Salazkin, Sergey N.
<x xml:space="preserve">Abstract</x> 1H and 13С NMR spectral assignments have been provided for low‐molecular reference monomers, poly(diphenyleneoxidephthalide) and periodic copoly(arylenephthalide) derivatives such as AB, ABB, and ABBB (where A = terphenylenephthalide and B = diphenyleneoxidephthalide) using 1H‐1H COSY, 1H‐13C HSQC and HMBC NMR techniques. Distinctive 13C NMR chemical shifts of a main chain have been observed containing fragments of similar structures and lateral phthalate groups being part of various diads. Copyright © 2013 John Wiley & Sons, Ltd.